REVIVAL OF MYSTICISM AND CONTEMPLATIVE PRAYER IN RELIGION - Vineeth, V F (Journal of Dharma, 2009)
Mysticism defies all definitions. This is mainly because it is not rational by nature. It is knowing God, the Ultimate Reality, by ‘touch’ rather than by thought. Though the expression ‘touching God’ may sound idiotic and contradictory, the mystics are fond of using expressions such as ‘to touch God’, ‘to taste and see that the Lord is good’ (Ps. 34:8). Here touching and tasting would primarily mean ‘to experience’. If God is God, the Ultimate Reality, the really Real (pāramārtikasatya), He awfully transcends all the powers and faculties of knowledge. Hence, knowing God who is by nature the Infinite and the Immortal one, by senses or mind, which are totally plunged into structures of limitation, is as foolish as trying to pour out the waters of a sea into a child’s playing pot. Though this audacity is obviously meaningless, mystics sometimes try to do this, or are led by the Spirit to try this, and prefer to remain baffled and tight-lipped, in silent admiration and salient wonder, even though they understand very little. But during these auspicious moments they do embrace more, experience more and desire to speak less and do more. Thus, mysticism is not a matter of crude obscurantism or fanaticism, over assertion of the thinking self, but a melting of the inner consciousness to be fused with the Divine, about which, St. Teresa of Avila says: “This prayer is a sleep of the faculties.”